(untitled) (Revista científica Olimpia, 2025)
Adapted Physical Activity (APA) emerges as an essential component for the comprehensive care of older adults with motor sequelae post-cerebrovascular diseases (CVD), given the increase in the prevalence of these pathologies and population aging. These conditions generate motor disabilities that negatively impact daily life activities (DLA) and the quality of life of this population group, requiring personalized interventions that transcend traditional approaches focused solely on physical rehabilitation according to context. Therefore, this article aims to design adapted physical exercises from Therapeutic Physical Culture (TPC), with the goal of optimizing functionality, emotional well-being, and social inclusion among these beneficiaries. Theoretical and empirical methods were employed, such as observation, analysis-synthesis, systemic structural functional analysis, measurement, as well as interview and survey techniques. Eleven beneficiaries with motor sequelae from cerebrovascular diseases (CVD) were selected, belonging to the Norte Popular Council in the municipality of Caimanera, in the province of Guantánamo, to whom adapted physical exercises were applied according to their needs and possibilities. Significant advances were achieved in the motor sphere, as the sequelae of the disease were reduced and functional performance improved, as evidenced during classes and in the tests conducted.